Is L'Uomo Nero is going off-topic (L'uomo nero. Materiali per una storia delle arti della modernità, 2023)
Following the usual tripartition of its sections into Monographic, Off-Topic, and Rarities, Rediscoveries and Recommendations, in the course of its twenty-year honourable career “L’uomo nero” has invitedits contributors to share research and reflections on certain themes and problems of history of contemporary art, choosing different approaches and according to a multiplicity of methods.For this new issue of the Open Access e-journal, the perspective is reversed and Off-Topic becomes the main topic of the issue, trying to feel in the airwhat is happening and in which direction research is moving, or simply to leave room for the “author’s choice”.
Keywords: Editorial; off-topic; author’s choice